Zakat Practices from the Times - Solahuddin Al-Ayubi; Evania Herindar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Zakat is an Islamic social financial instrument that has become an important factor in overcoming poverty. This paper aims to explain the practice of zakat from time to time: the practice of zakat on the Prophet Muhammad, during the Khulafaurrasyidin era, during the tabi'in period, during the Islamic Kingdom in Indonesia, during colonialism, and after independence. This article uses a approach qualitative. This article is library research. The results showed that the management of zakat on the Prophet Muhammad Saw. until khulafaurrasydin was handed over directly to the Prophet Muhammad Saw. and Khulafaurrasyidin or people who are mandated by the Prophet and Khulafaurrasyidin to manage them. The management of zakat in the Umayyah dynasty is getting better, but its performance has declined except during the time of Umar bin Abdul Aziz. During the Abbasiyah dynasty, people began not paying zakat due to the high burden of kharj and ushr taxes. In the Andalusian dynasty, the management of zakat became a bone of contention between tribal chiefs, as a result, the distribution of zakat could not meet the adequacy of the poor. During the Fatimiyah dynasty, the caliph asked each regional head to collect zakat, then deposited the zakat to him without any recording of expenses or receipts. The most important lesson in this era is that public trust and compliance in paying the zakat are the main determinants of zakat performance. During the Islamic Kingdom, zakat became a public obligation and contributed to the development of Islamic kingdoms. Then the zakat is managed by the kingdom and is considered as royal income. During colonialism, zakat served as a source of funds for the struggle for Indonesian independence. After Indonesia gained its independence, zakat again received attention from economists, fiqh experts, and the government in the Indonesian economy.